Technical and economic parameters of CO₂ capture from power plant flue gases - Kovacs, F. (NTU "KhPI", 2009)
The paper investigates the technical and economic (cost) parameters of the release, capture and disposal of CO₂ from the flue gases of power plants using fossil fuels (coal, naturalgas), making comparisons and generalisations on the basis of the analysis of a wide range of data in the literature. First, the paper gives reasons why the topic is a hot issue and proves the role of fossil fuels in future energy supply with forecast data. During the technological improvement of power plants in the last 50 years, block capacity has shown a considerable, 5-8 times in crease with thermal efficiency in creasing by 50-60%, resulting in a 30-40% decrease in specific carbon dioxide release. The paper briefly refers to the theoretical possibility of the sequestrationof CO₂ in geological formations. The effects of the implementation of CO₂ capture on increasing investment costs and decreasing fuel utilisation (thermal) efficiency are analysed. The efficiency of CO₂ capture and the parameters of atmospheric carbon dioxide emission are given for the different fuel types and technological solutions. In relation to the technological solutions of capture, it is indicated what amount of specific costs (USD/tCO₂) is expected for CO₂ capture-avoidance and to what extent the costs of electric energy production are increased by capture-avoidance.
Технические и экономические параметры использования CO₂ в электростанциях